INTERACTIVE MULTIMEDIA ON LOCAL LANGUAGE LEARNING OF ELEMENTARY SCHOOL IN SURAKARTA CITY - Daryanto, Joko; Karsono, Karsono (Universitas Pendidikan Indonesia, 2019)
This research about the use of interactive multimedia in Local Language Learning in the Elementary School in Surakarta region aimed to find out the effectiveness of the use interactive multimedia in the Wayang Purwa and Javanese script topics. This research applied research and development (RD) method with one-group pretest-posttest experimental design. The data were collected using tests. The validity test comprised of instrument and content validation. The results of the treatment to the third-grade students of SD Negeri Karangasem III Surakarta in the topic of Wayang Purwa showed that the average score in the pre-cycle, first cycle, and second cycle always increased. In the pre-cycle, the students' average score was 54.9 with the completeness percentage of 31.2 %. The average score after the treatment in the first cycle was 72.34 with the completeness percentage of 71.88 and in the second cycle was 81.27 with the completeness percentage of 90.63 %. The same results were also obtained in the topic of Javanese script in the second-grade students of SD Tunggulsari II Surakarta indicating that the average score of pre-cycle, first cycle, and second cycle always increased. The classical completeness percentage in the pre-cycle of 6.25 % increased to 56.25 % in the first cycle and 93.75 in the second cycle. The conclusion is that the used of interactive multimedia can improve the skills of Wayang Purwa storytelling and Javanese-script writing.